A Pilot Profile of the Social Entrepreneur in the Constantly Changing Romanian Economy - Gabriela Ţigu; Maria-Cristina Iorgulescu; Anamaria Sidonia Răvar; Ramona Lile (Amfiteatru Economic Journal, 2015)
Social economy and social entrepreneurship are concepts subject of much debate in the academic environment, as their importance is growing in the present times, when the public sector and business environment alike have demonstrated their incapacity to solve specific social problems, such as conserving local traditions and biodiversity or insertion into the labour market of people from vulnerable groups. This article focuses on social entrepreneurs, by aiming to identify their main motivations in the founding and development of a social enterprise, as well as the main challenges faced in their social entrepreneurial activity in a constantly changing business environment. The paper presents a qualitative research conducted on Romanian social entrepreneurs. The results, interpreted through content analysis, indicate that social entrepreneurs, unlike business entrepreneurs, are not profit-driven, but mission driven, their main objective being to make a difference in the society and have a positive impact in the local communities. Furthermore, the research revealed specific challenges faced by Romanian social entrepreneurs, as well as specific differences between social and business entrepreneurs, who aim strictly achieving economic performance. Considering the limitations and future research directions, the implications of the findings are discussed, the paper outlining a profile of the social entrepreneur that can be useful to the public sector for the development of policies aimed at enhancing this type of entrepreneurship, in a constantly changing social environment.
Keywords: L26; L31; D71; D73; 330; social economy; dynamic business environment; changing social environment; social entrepreneur; business entrepreneur; motivation